Pengaruh Family Structure Terhadap Materialisme Dan Pembelian Kompulsif Pada Remaja - Ristianawati Dwi Utami (Universitas Airlangga, 2011)
The main issue of this study is how family structure influences on consumer behavior. In this study both family structure intact, disrupted family structure and family structure associated with the attitude of materialism and compulsive buying with family stressors and family resources as mediating variables and socioeconomic status as a moderating variable. The purpose of this study is (1) to determine differences in attitude of materialism and compulsive buying among teenagers who come from intact family with a disrupted family, (2) to measure the influence of family resources and family stressors on the attitude of materialism and compulsive buying in adolescents and (3) for measure the effect of family structure on family resources and family stressors when moderated by socioeconomic status variables. Samples of this study are adolescents aged 11-16 years who live in the city of Yogyakarta. Number of samples consisted of 97 teenagers who come from the intact family structure and 38 teenagers who come from disrupted family structure. The results showed that there were differences in the attitude of materialism and compulsive buying among teenagers who come from intact family with a disrupted family. Teenagers who come from disrupted family and compulsive tend to be more materialistic than adolescents from intact family. The study also found that family resources and family stressors shown to affect the materialism and compulsive buying in adolescents. Effect of family structure on family resources, moderated by socioeconomic status. While the influence of family structure on family stressors. Not moderated by socioeconomic status.